Deliberative Value-Based Education in realizing the Tahfidz Al-Quran generation at MIN 3 Central Tapanuli - Ismail Ismail; Sugeng Sukoco; Syafaruddin Syafaruddin; Nurul Oktaviana Mekawati (Edukasi Islami : Jurnal Pendidikan Islam, 2021)
The purpose of writing this article is to see how the planning and arrangement of education based on the value of deliberation at MIN 3 Central Tapanuli in realizing the Tahfidz Al-Quran generation in the era of globalization. This research uses descriptive qualitative. This is done to be able to describe the decisions taken in realizing the Tahfidz Al-Quran generation. The author uses three stages of data analysis: data analysis before in the field, data analysis in the area, and data analysis after completion in the field. To test the validity of the data, it is done in three ways, namely triangulation, member check, and doing a detailed description. The study results provide answers that: 1) The Planning Stage of the MIN 3 Tapanuli Tengah School uses organization, forum, structure, function, and mechanism so that planning and supervision have clear standards and goals. 2) Planning Preparation Stage in improving the quality of education at MIN 3 TAPTEG, the Principal communicates to embrace all stakeholders in this madrasa, including the leadership staff, namely by opening communication to anyone. 3) Realizing the Tahfidz Al-Quran Generation in the Era of Globalization, the school uses three methods: Semaan, reading together, and sorongan.